Tumour heterogeneity: a problem in biopsy assessment of the proliferation index of oesophageal adenocarcinomas. Issue 1 (February 1996) - Jenner, K; Darnton, S J; Billingham, L; Warfield, A T; Matthews, H R
Abstract : Tumour heterogeneity may pose a problem when biopsy specimens are taken to measure proliferation (for example, in assessing response to therapy). Two "biopsy specimens" were taken from the centre and two from the edge of the luminal surface of 20 resected oesophageal adenocarcinomas. The proliferation index for each "biopsy specimen" was measured by counting Ki67 labelled nuclei in histological sections. The proliferation index was not associated with tumour differentiation or stage. There was site specific heterogeneity with a significant difference in proliferation index between the central (mean (SD) 36·4 (9·7)) and edge "biopsy specimens" (39·3 (9·9)). There was, however, a wide range of differences between pairs of "biopsy specimens" from both sites. In conclusion, if a tumour is to be sampled for measurement of the proliferation index before and after treatment, then the sequential biopsy specimens (preferably duplicated on each occasion) should be taken consistently from a leading edge of the lesion.